Unilateral hindlimb casting induced a delayed generalized muscle atrophy during rehabilitation that is prevented by a whey or a high protein diet but not a free leucine-enriched diet. - Hugues Magne; Isabelle Savary-Auzeloux; Carole Migné; Marie-Agnès Peyron; Lydie Combaret; Didier Rémond; Dominique Dardevet (PLoS ONE, 2013)
Sarcopenia is the general muscle mass and strength loss associated with ageing. Muscle atrophy could be made worse by exposure to acute periods of immobilization, because muscle disuse by itself is a stimulus for atrophy. Using a model of unilateral hindlimb casting in old adult rats, we have already demonstrated that the primary effect of immobilization was atrophy in the casted leg, but was also surprisingly associated with a retarded atrophy in the non-casted leg during rehabilitation. In search of mechanisms involved in this generalized atrophy, we demonstrated in the present study that contrary to pair-fed non-immobilized control animals, muscle protein synthesis in the non-immobilized limb was unable to adapt and to respond positively to food intake. Because pair-fed control rats did not lose muscle mass, this defect in muscle protein synthesis may represent one of the explanation for the muscle mass loss observed in the non-immobilized rats. Nevertheless, in order to stimulate protein turn over and generate a positive nitrogen balance required to maintain the whole muscle mass in immobilized rats, we tested a dietary free leucine supplementation (an amino acid known for its stimulatory effect on protein metabolism) during the rehabilitation period. Leucine supplementation was able to overcome the anabolic resistance in the non-immobilized limb. A greater muscle protein synthesis up-regulation associated with a stimulation of the mTOR signalling pathway was indeed recorded but it remained inefficient to prevent the loss of muscle in the non-immobilized limb. By contrast, we demonstrated here that whey protein or high protein diets were able to prevent the muscle mass loss of the non-immobilized limb by sustaining muscle protein synthesis during the entire rehabilitation period.